Growth performance and fatty acid profiles of Malaysian mahseer, Tor tambroides (Bleeker, 1854) fed with different types of palm oil and riverine fruit oil - Bami, Mahkameh Lashkarizadeh (2017)
This study was carried out to investigate the effects of various dietary oil sources containing different types of palm oil and riverine fruit oils on the growth performance, proximate composition and tissue fatty acid profile of juvenile Malaysian mahseer, Tor tambroides. Domesticated wild caught T. tambroides juveniles were used in all feeding trials. Each feeding trial was conducted for a period of 12 weeks and treatments were triplicated. In Experiment 1, four isocaloric and isonitrogenous diets with 5% lipid from different types of palm oil [crude palm oil (CPO), refined bleached deodorized palm oil (RBDO), refined bleached deodorized palm olein (RBDPO) and refined bleached deodorized palm stearin (RBDPS)] were tested. Although the growth performance of fish fed CPO was similar to those fed refined products, its muscle contained significantly higher n-3 fatty acids. Thus, CPO was used as the control in the subsequent feeding trials.